The Use of Technology Based on Google Suite for Education at SMP Negeri 5 Surakarta: Penggunaan Teknologi Tepat Guna Berbasis Google Suite For Education di SMP Negeri 5 Surakarta - Hasan Dwi Cahyono; Dewi Wisnu Wardani; Haryono Setiadi; Ardhi Wijayanto (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has a major impact on the education sector. Educators are necessarily assisted to ensure that the educational process can run well in any foreseen condition. Technology-based learning can be seen as a solution to this problem at SMP Negeri 5 Surakarta (SMPN 5 Surakarta) in these regards. However, the use of technology needs to be decided carefully to minimize any disadvantageous. SMPN 5 Surakarta has been facilitated with Google Suite for Education (GSE)-based services with an integration into the nation-wide @belajar.id platform. Furthermore, the Community Service Team for Research Group Data Information Knowledge and Engineering (PkM RG DIKE Team) UNS mandated a training on how to fully implement the platform. As this program was aimed at establishing a sustainable partnership with the community, we hope that SMPN 5 Surakarta can further promote the obtained experience from the PkM DIKE UNS Team to the surrounding regions. Abstrak Dampak pandemi COVID-19 tidak hanya dirasakan oleh siswa, tetapi juga para pendidik. Pendidik tentu berkewajiban agar proses pendidikan dapat berjalan dengan baik pada berbagai kondisi. Pembelajaran berbasis teknologi bisa menjadi solusi permasalahan ini di SMP Negeri 5 Surakarta. Namun, pemilihan teknologi yang tepat perlu dilakukan karena dapat berakibat kekurang-optimalan dalam proses pembelajaran. Pada layanan teknologi ini, sekolah bisa dengan mudah melakukan menggunakan layanan berbasis Google Suite for Education (GSE) yang telah terintegrasi ke platform @belajar.id. Selanjutnya, Tim Pengabdi kepada Masyarakat Research Group Data Information Knowledge and Engineering (Tim PkM RG DIKE) UNS memberikan pelatihan tentang cara penggunaan platform tersebut. Agar program ini dapat memberikan keberlanjutan dari program kemitraan bersama masyarakat, kami berharap bahwa pihak SMP Negeri 5 Surakarta bisa menyebarkan keterampilan yang didapat dari TIM PkM DIKE UNS kepada para pendidik di sekitar Surakarta.